Enhancing SME’s Performance based on Innovation Culture, Innovation Capability, and Strengthened by the External Environment - Indrawati, Nur Khusniyah; Alfathya, Atmaya Fitra (Fakultas Ekonomi Universitas Kadiri, 2024)
a